Long-term mechanical performance of high fluidity fiber reinforced concrete modified by metakaolin - Dou, Hui; Xu, Huaxin; Xie, Junjie (Frontiers in Materials, 2023)
To clarify the long-term strength and toughness of metakaolin (MK) and steel fiber (SF) modified concrete with higher fluidity and water/binder ratio, a series of tests including slump tests, compression tests, splitting tests, digital image processing and Scanning Electron Microscope (SEM) tests were performed on MK-SF concrete cured for 7-360 days. Results reveal that the slump of fresh concrete decreased with increase in the MK and SF replacement rates. Moreover, the impact of MK on the slump of steel fiber reinforced concrete (SFRC) was more pronounced when combined with a lower water/binder ratio, resulting in increased viscosity. At pre-peak stress region of strain-stress curve, the compressive strength fc, tensile strength ft, Young's modulus Ec, elastic modulus E0 and tensile strain at peak stress εt-max of high fluidity MK-SF concrete increased with increasing MK and SF admixing ratio, regardless of curing age. Notably, the coupling effects of MK and SF became more prominent after long-term curing. Without MK incorporation, the effects of SF and curing time on above indices were relatively implicit. At post-peak stress region of strain-stress curves, there existed a residual stage. The inclusion of MK significantly improved the long-term residual strength and strain of SFRC. Additionally, the toughness index Mc, which represents the total area of the compressive strain-stress curve containing both the pre-peak and post-peak regions, also exhibited substantial development with curing time, primarily attributed to the incorporation of MK and SF. The coupling of MK and SF led to a transformation of the concrete failure mode from brittle to ductile. Regression analysis reveals that a linear equation adequately described the long-term relationships of fc- ft, fc-Ec, fc-E0, fc-Mc and fc-εt-max in MK modified SFRC. Based on the testing data, a relative strength or toughness index λ and a new generalized hyperbola model were proposed to predict the long-term mechanical behavior mentioned above. Through crack morphology and microstructure analysis, the distinct roles of MK and SF in the composite material were examined.